Cathelicidin antimicrobial peptides in cod and salmon - Broekman, Daniela C., 1980- (2012)
Cathelicidins are a family of antimicrobial peptides that have been well researched in mammals, where they have been described to have an important role in immunity. Cathelicidins are ubiquitous among vertebrates having been found in fish, amphibia, reptiles, birds and mammals including marsupialia thereby demonstrating their conserved position throughout evolution. The Atlantic cod Gadus morhua is an economically important fish in Iceland. In this thesis the focus is on the cod cathelicidin „codCath“. It was in the course of this project isolated from cod and then characterized regarding its activity and regulation. A cathelicidin antimicrobial peptide was isolated from cod head kidney by high-performance liquid chromatography. The mature peptide was sequenced at the N-terminus and a total size of 67 amino acids was deduced. The peptide has a predominance of the amino acids serine, arginine and glycine, a positive charge of +15 and is considered a novel and unique cathelicidin. Both the isolated and the synthetic peptide demonstrated antibacterial activity. The synthetic peptide helped to identify a salt sensitivity of this peptide with reduced activity at high salt concentrations. Our results indicated that the mode of activity of codCath was rapid lysis of bacterial cells, while it was selectively active towards microbial but not eukaryotic membranes. The peptide was degraded and inactivated by extracellular products of pathogenic bacteria. Cod cathelicidin transcripts were found in eggs and larvae of Atlantic cod and in larvae levels were responsive to environmental stimuli. In a salmonid cell line cathelicidin was significantly upregulated through Gram-negative bacteria and flagellin and in a gadoid cell line through Lactobacillus sp. and poly(I:C). The responsiveness through microbial PAMPs indicates signaling through TLRs or other receptors. The inhibition of the PI3K further indicated that this protein has an inhibitory role on receptor mediated signaling and is involved in the signaling cascade to ...